Does the journal impact factor predict individual article citation rate in otolaryngology journals? - Hussain, Salman; Almansouri, Abdullah; Allanqawi, Lojaine; Philteos, Justine; Wu, Vincent; Chan, Yvonne (Ear, nose, & throat journal, 2025)
Objective Citation skew is a phenomenon that refers to the unequal citation distribution of articles in a journal. The objective of this study was to establish whether citation skew exists in Otolaryngology—Head and Neck Surgery (OHNS) journals and to elucidate whether journal impact factor (JIF) was an accurate indicator of citation rate of individual articles. Methods Journals in the field of OHNS were identified using Journal Citation Reports. After extraction of the number of citations in 2020 for all primary research articles and review articles published in 2018 and 2019, a detailed citation analysis was performed to determine citation distribution. The main outcome of this study was to establish whether citation skew exists within OHNS literature and whether JIF was an accurate prediction of individual article citation rate. Results Thirty-one OHNS journals were identified. Citation skew was prevalent across OHNS literature with 65% of publications achieving citation rates below the JIF. Furthermore, 48% of publications gathered either zero or one citation. The mean and median citations for review articles, 3.66 and 2, respectively, were higher than the mean and median number of citations for primary research articles, 1 and 2.35, respectively (P < .001). A statistically significant correlation was found between citation rate and JIF (r = 0.394, P = 0.028). Conclusions The current results demonstrate a citation skew among OHNS journals, which is in keeping with findings from other surgical subspecialties. The majority of publications did not achieve citation rates equal to the JIF. Thus, the JIF should not be used to measure the quality of individual articles. Otolaryngologists should assess the quality of research through the use of other metrics, such as the evaluation of sound scientific methodology, and the relevance of the articles.